2023
DOI: 10.1002/bab.2451
|View full text |Cite
|
Sign up to set email alerts
|

Banxia Xiexin decoction ameliorates dextran sulfate sodium (DSS)‐induced ulcerative colitis via inhibiting serine‐threonine protein kinase (Akt)/mitogen‐activated protein kinase (MAPK) signaling pathway

Abstract: Banxia Xiexin decoction (BXD), a traditional Chinese medicine, was widely used in treating ulcerative colitis (UC). However, the active components of BXD and its mechanism in UC remain elusive. Therefore, we used network pharmacology in vivo experiments, molecular docking, and surface plasmon resonance strategy (SPR) to uncover BXD's potential mechanism. A UC rat model was established by orally administering 7% dextran sulfate sodium (DSS) in drinking water, BXD and palmatine were orally administered for 7 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Further study indicated that BXD suppressed Akt/IκBα kinase activity through NF-κB activation, blocking ERK expression and subsequently suppressing NF-κB p65 activation, which notably reduced the production of inflammatory factors including TNF-α, IL-1β, IL-6, and IL-8. More importantly, the proteins upstream and downstream of the Akt/MAPK signaling pathway prevent the tissue damage caused by inflammatory cytokines by preventing cellular signals from being amplified and by efficiently suppressing additional signal transmission [197]. Interestingly, the different decoction methods can bring the difference in the pharmacological effects of traditional herbal prescriptions.…”
Section: Banxia Xiexin Decoction (Bxd)mentioning
confidence: 99%
See 2 more Smart Citations
“…Further study indicated that BXD suppressed Akt/IκBα kinase activity through NF-κB activation, blocking ERK expression and subsequently suppressing NF-κB p65 activation, which notably reduced the production of inflammatory factors including TNF-α, IL-1β, IL-6, and IL-8. More importantly, the proteins upstream and downstream of the Akt/MAPK signaling pathway prevent the tissue damage caused by inflammatory cytokines by preventing cellular signals from being amplified and by efficiently suppressing additional signal transmission [197]. Interestingly, the different decoction methods can bring the difference in the pharmacological effects of traditional herbal prescriptions.…”
Section: Banxia Xiexin Decoction (Bxd)mentioning
confidence: 99%
“…This may be a reason why BXD exerts multifunctional effects on the brain-gut axis. [192,196,197,201].…”
Section: Banxia Xiexin Decoction (Bxd)mentioning
confidence: 99%
See 1 more Smart Citation